VARIABILITAS SUHU DAN SALINITAS DI PERAIRAN CISADANE - Hadikusumah, Hadikusumah (UI Scholars Hub, 2008)
The Temperature and Salinity Variabilities at Cisadane Estuary. The study was conducted at Cisadane Estuary at 18 oceanographic station in Transition Monsoon Season I, East Monsoon Season, and Transition Monsoon Season II from 2003 to 2005. The area of the study was located at the longitude of 106.58° - 106.70° E and the latitude of 5.96° - 6.02°S. The measurements of temperature, salinity, tubidity and light transmision used CTD (Conductivity, Temperature and Depth) Model SBE-19. The result shows that the temperature and salinity vertical profil variabilities at Cisadane Estuary underwent a change in the influence of Transition Monsoon Season I, East Monsoon Season, and Transition Monsoon Season II, for example it was obtained the leg time of the maximum salinity of Transition Monsoon Season II as the same as that of East Monsoon Season. Based on the horizontal and vertical distribution pattern analysis of the interaction between low salinity fresh water of Cisadane River and high salinity sea water of Java Sea, it was also influenced by the season variability and tide. The surface layer was much more influenced by the low salinity and the heat of sunray (seasonal variability) with the weaker intensity to the lower layer. The change of the heat energy by the increase of seasonal temperature occurred in September 2003 to May 2004 ((∆E = 600.6 ⋅ 105 Joule), July to November 2005 (∆E = 84.9 Joule). The decrease of the heat energy occurred in June to September 2003 ((-267.6 ⋅ 105 ), May ke October 2004 (∆E = 189.3 ⋅ 105 Joule) and October 2004 to July 2005 (∆E = -215.4 ⋅ 105 Joule).